2009
DOI: 10.1016/j.joca.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A 5 year prospective study of patient-relevant outcomes after total knee replacement

Abstract: Compared to preoperatively, a significant improvement was still seen 5 years postoperatively. However, the best result was reported at 1 year, indicating a decline from 1 to 5 years after TKR. To fully evaluate the results of TKR with regard to pain and PF, follow-ups longer than 2 years are needed, and items of more demanding PFs should be included. Older age to some extent predicted more postoperative pain and other symptoms, however, no predictors of postoperative PF were found, indicating the difficulty of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
136
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(156 citation statements)
references
References 16 publications
12
136
3
5
Order By: Relevance
“…This result contradicts the conclusions of a previous longitudinal study in which the best functional and clinical outcomes were obtained within 12 months, followed by significant deterioration in terms of function, pain and vitality at 5 years [10]. Complementary studies should be designed to determine the long-term evolution of patient-reported symptoms, function and satisfaction after TKR.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This result contradicts the conclusions of a previous longitudinal study in which the best functional and clinical outcomes were obtained within 12 months, followed by significant deterioration in terms of function, pain and vitality at 5 years [10]. Complementary studies should be designed to determine the long-term evolution of patient-reported symptoms, function and satisfaction after TKR.…”
Section: Discussioncontrasting
confidence: 75%
“…Over the last 3 decades, long-term follow-up studies reported constant improvement in implant survival [2][3][4][5][6][7][8]. In parallel, several prospective studies highlighted significant clinical and functional improvement on composite scores such as Knee injury and Osteoarthritis Outcome Score (KOOS) [9,10], Knee society score (KSS) [11,12], and Western Ontario and McMaster osteoarthritis index (WOMAC) [13,14], or reported satisfaction rates exceeding 80% [14][15][16], confirming that TKR outcomes are generally good. However, in long-term follow-up, orthopaedic surgeons and also GPs and rheumatologists may face some patients who do not find the operated knee totally natural despite absence of functional limitations or pain.…”
Section: Introductionmentioning
confidence: 99%
“…This trend undoubtedly will continue as we support an increasingly aging population and perform primary surgery on a more demanding younger population [6]. Primary TKA almost uniformly relieves pain, improves knee function, and produces levels of patient satisfaction greater than 80% [2,17,21,24,26,28,[32][33][34]. Revision surgery is less predictable, with lower rates of survival, increased rates of complications, varied patient satisfaction, and an inconsistent ability to restore or improve quality of life [8,12,18,29].…”
Section: Introductionmentioning
confidence: 99%
“…As careful followup is needed in these high activity patients, the Knee Society added evaluation items for patients with sports activities in the new Knee Society Knee Scoring System [24]. KOOS sports activities consist of "jumping" and "running", and these items made it possible to evaluate the knee function and symptoms in high activity patients which KOOS ADL could not [25]. KOOS would be a good parameter for activities in highly active patients such as younger patients after TKA.…”
Section: Discussionmentioning
confidence: 99%